Higher sense of coherence is associated with better mental and physical health in emergency medical services: results from investigations on the revised sense of coherence scale (SOC-R) in rescue workers. Issue 1 (1st January 2019) - Behnke, Alexander; Conrad, Daniela; Kolassa, Iris-Tatjana; Rojas, Roberto
ABSTRACT: As rescue workers are regularly confronted with potentially traumatising on-duty events, they have an increased risk to develop trauma-related mental and physical health impairments, including post-traumatic, depressive, and somatic symptoms. For this high-risk group, it could be of particular importance to experience their occupational burden as manageable, meaningful, and coherent. This mindset – called sense of coherence – may be a potential resilience factor against the development of mental and physical health problems. In a cross-sectional cohort of 102 rescue workers ( Mdn ( QD )age = 26.0 (8.5), age range: 18−61), including 36 women, we investigated whether higher values on the Revised Sense of Coherence Scale (SOC-R) predicted lower post-traumatic, depressive, and somatic symptoms. In addition, we evaluated the factor structure of the SOC-R using confirmatory factor analyses. Linear regressions indicated that higher SOC-R, but particularly manageability scores were associated with less post-traumatic (β = −.31, p = .009), depressive (β = −.44, p < .001), and somatic symptoms (β = −.36, p = .002). Furthermore, we found that all symptom scores significantly increased with occupational and private-life trauma exposure. The SOC-R's factor structure was replicated, comprising the three subscales manageability, reflection, and balance. However, the SOC-R's convergent factor validity was rather low in the present sample. Taken together, a high sense of coherence, and in particular a high manageability conviction, was observed as resilience factors for high-risk groups that are frequently exposed to potentially traumatic events. Future studies might investigate whether strengthening the sense of coherence could be one building block in an effective prevention program for maintaining long-term health in risk groups.